(untitled) (Mason, OH, 2008)
PROFESSIONAL SELLING: A TRUST BASED-APPROACH, 4e is written specifically for you the student. It strives to provide comprehensive coverage of sales tools and tactics in a way that you will find interesting, readable, and enjoyable. The text is arranged into ten modules, which blend research results with up-to-date professional selling practice in a format designed to stimulate learning. "Objectives" highlight the basic material you will want to learn. Chapter opening vignettes illustrate many of the significant ideas to be covered in the upcoming module. These vignettes use real-world examples to illustrate the diversity and complexity of professional selling. Key words, highlighted in bold, are used to illustrate key concepts and definitions. A final module summary is geared to the learning objectives at the beginning of each chapter. If you understand professional selling terms, develop selling knowledge, and build professional sales skills, you will be prepared to make successful, professional selling decisions
Keywords: Selling,Nghệ thuật bán hàng